Assessment of Cytospora Isolates From Conifer Cankers in China, With the Descriptions of Four New Cytospora Species - Pan, Meng; Zhu, Haiyan; Tian, Chengming; Huang, Manrong; Fan, Xinlei (Frontiers in Plant Science, 2021)
Cytospora species are widely distributed and often occur as endophytes, saprobes or phytopathogens. They primarily cause canker and dieback diseases of woody host plants, leading to the growth weakness or death of host plants, thereby causing significant economic and ecological losses. In order to reveal the diversity of Cytospora species associated with canker and dieback diseases of coniferous trees in China, we assessed 11 Cytospora spp. represented by 28 fungal strains from symptomatic branches or twigs of coniferous trees, i.e., Juniperus procumbens, J. przewalskii, Picea crassifolia, Pinus armandii, P. bungeana, Platycladus orientalis in China. Through morphological observations and multilocus phylogeny of ITS, LSU, act, rpb2, tef1-α, and tub2 gene sequences, we focused on four novel Cytospora species (C. albodisca, C. discostoma, C. donglingensis, and C. verrucosa) associated with Platycladus orientalis. This study represented the first attempt to clarify the taxonomy of Cytospora species associated with canker and dieback symptoms of coniferous trees in China.